Is prescription of specific movement form necessary for optimal skill development? A nonlinear pedagogy approach - Lindsay, R. S.; Komar, J.; Chow, J. Y.; Larkin, P.; Spittle, M. (Research Quarterly for Exercise and Sport, 2023)
Purpose Nonlinear Pedagogy (NLP) proposes that skill development is a nonlinear process, advocating the integration of variability into practice to facilitate individualized movement patterns. However, the influence of a NLP for skills that emphasize a specific movement form is relatively unknown. This study aimed to investigate the impact of a NLP approach when learning a movement form based skill.